2018
DOI: 10.21873/anticanres.12286
|View full text |Cite
|
Sign up to set email alerts
|

PDGFRα/HER2 and PDGFRα/p53 Co-expression in Oral Squamous Cell Carcinoma

Abstract: Our study revealed that PDGFRα/HER2 and PDGFRα/p53 co-expression exists in poorly differentiated OSCCs, suggesting that cooperation between these proteins might enhance aggressive behavior of tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…Many studies have reported no Her-2 expression, while others have found no worthy correlations in OSCC [ 32 , 34 36 ]. In other works, however, overexpression of Her-2 has been associated with significantly shorter overall survival, higher clinical and nodal stage, and metastasis of OSCC patients [ 37 – 40 ]. Similarly, we found shorter overall survival in Her-2 positive vs negative patients.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have reported no Her-2 expression, while others have found no worthy correlations in OSCC [ 32 , 34 36 ]. In other works, however, overexpression of Her-2 has been associated with significantly shorter overall survival, higher clinical and nodal stage, and metastasis of OSCC patients [ 37 – 40 ]. Similarly, we found shorter overall survival in Her-2 positive vs negative patients.…”
Section: Discussionmentioning
confidence: 97%